WAKTU SHALAT PERSPEKTIF SYAR‘I - Tamhid Amri (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2015)
Prayer is one of the obligations of a believer to his God, prayer has various virtues and wisdom, both in terms of religious, psychological, and social. Thus, prayer is the most important worship in Islam. In carrying out prayer, Muslims should not be carelessly, it is because prayer is worship predetermined time and how. In modern times, we are not going to be difficult in knowing the prayer time because many Islamic organizations, even governments make prayer schedule as a reference in the salat. Nevertheless, we need to know the time of prayer based on a naturally occurring phenomenon, so that our knowledge is more comprehensive. In its implementation, some scholars have the same opinion in the interpretation of the hadith about prayer timings exemplified by the Prophet. But there are also some scholars have different opinions about the interpretation for the determination of some prayer time. As an example the opinion of Imam Shafi'i and Imam Hanafi about the start time of Asr and Isha prayer which different opinions in the interpretation of the hadith of the Prophet Muhammad.